Effects of Feeding Spodoptera littoralis on Lima Bean Leaves. II. Continuous Mechanical Wounding Resembling Insect Feeding Is Sufficient to Elicit Herbivory-Related Volatile Emission - Mithöfer, Axel; Wanner, Gerhard; Boland, Wilhelm (Plant physiology (Bethesda), 2005)
Herbivore feeding elicits defense responses in infested plants, including the emission of volatile organic compounds that can serve as indirect defense signals. Until now, the contribution of plant tissue wounding during the feeding process in the elicitation of defense responses has not been clear. For example, in lima bean (Phaseolus lunatus), the composition of the volatiles induced by both the insect caterpillar Spodoptera littoralis and the snail Cepaea hortensis is very similar. Thus, a mechanical caterpillar, MecWorm, has been designed and used in this study, which very closely resembles the herbivore-caused tissue damage in terms of similar physical appearance and long-lasting wounding period on defined leaf areas. This mode of treatment was sufficient to induce the emission of a volatile organic compound blend qualitatively similar to that as known from real herbivore feeding, although there were significant quantitative differences for a number of compounds. Moreover, both the duration and the area that has been mechanically damaged contribute to the induction of the whole volatile response. Based on those two parameters, time and area, which can replace each other to some extent, a damage level can be defined. That damage level exhibits a close linear relationship with the accumulation of fatty acid-derived volatiles and monoterpenes, while other terpenoid volatiles and methyl salicylate respond in a nonlinear manner. The results strongly suggest that the impact of mechanical wounding on the induction of defense responses during herbivore feeding was until now underestimated. Controlled and reproducible mechanical damage that strongly resembles the insect's feeding process represents a valuable tool for analyzing the role of the various signals involved in the induction of plant defense reactions against herbivory.